Pengaruh Perbandingan Tepung Ketan dan Daging Buah Naga Merah (Hylocereus polyrhizus) Terhadap Kualitas Dodol Buah - R.Agung Surya Prabowo; Akhyar Ali; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study was to determine the best ratio of Glutinous flour and Red dragon fruit (Hylocereus polyrhizus) towards the quality of fruit dodol. The experiment was arranged by the Randomized Complete Design (RCD) with four treatments : T1N1 = 1:1 (50% Glutinous flour, 50% Red dragon fruit); T2N2 = 1:0,8 (55,56% Glutinous flour, 44,44% Red dragon fruit); T3N3 = 1:0,6 (62,5% Glutinous flour, 37,5% Red dragon fruit) dan T4N4 = 1:0, (71,43% Glutinous flour, 28,57% Red dragon fruit). The result of this study showed the ratio of glutinous flour and red dragon fruit affected on water content, ash content, crude fiber content, colour, flavor, texture and overall acceptance of fruit dodol. It was concluded the treatment of T4N4 (71,43% Glutinous flour, 28,57% Red dragon fruit) produce dodol with the best quality towards: water content 16,54%; ash content 0,21%; crude fiber content 0,93%. Keyword: Dodol, Glutinous flour and Red dragon fruit